Passenger Information Systems in Public Transport - Ivana Olivkova (Communications - Scientific letters of the University of Zilina, 2008)
The article deals with establishment of passenger information systems which are comprehensive and not limited to one or more individual operators or transport modes. The systems should be multi-lingual, disabled adapted, both inside and outside interchanges, and combine static (i.e. timetable) and dynamic data on both public and private transport services.